The Analyse of Online Exercises of Aspekte Neu B2 - Nurhani, Nuki; Hafdarani; Muthmainah, Nur (Nusantara Science and Technology Proceedings)
During the pandemic, the teaching profession faces substantial challenges with regard to the switch from in-classroom teaching to online formats, requiring adjustments in planning, work methods, course design etc. Teachers need materials such as books and exercise papers which are suitable and adequate for online courses. So far, the exercise book Aspekte Neu B2 which was designed for in-classroom teaching is being used in a number of universities and language institutes in Indonesia. Whether it can also be used for online courses deserves to be scrutinized. This study solely examines the usage of Aspekte Neu B2 in respect of online classes. The aim is to determine to which degree it meets the general requirements of the Kriterienkatalog für Internet Lernmaterial Deutsch als Fremdsprache (list of criteria in respect of internet learning tools for German as a foreign language). The underlying research method of this study is the qualitative, ie. descriptive-analytical method. Only the online exercises of Aspekte Neu B2 were taken into consideration, ie. not the digital version of the course book. Results indicate that 55.4% of the book’s online exercises are in compliance with general criteria referring to technique, interactivity, exercise & quests, as well as feedback. It was not required for this study for an online exercise to fulfill all of the listed criteria. However, it was found that the online exercises of the book should be adapted to the online formats. That, at least, would help instructors choosing relevant training material for their online classes.